Therapeutic Mechanisms of Berberine to Improve the Intestinal Barrier Function via Modulating Gut Microbiota, TLR4/NF-κ B/MTORC Pathway and Autophagy in Cats - Cao, JingWen; Chen, MiaoYu; Xu, Ran; Guo, MengYao (Frontiers in Microbiology, 2022)
Background Inflammatory bowel disease (IBD), a disease that seriously harms human and animal health, has attracted many researchers' attention because of its complexity and difficulty in treatment. Most research has involved rats and dogs, and very little was cats. We should know that gut microbiota varies significantly from animal to animal. Traditional Chinese Medicine and its monomer component have many advantages compared with antibiotics used in pet clinics. Numerous studies have shown berberine (berberine hydrochloride， BBr) therapeutic value for IBD; however, the specific mechanism remains to consider. Results We assessed gut pathology and analyzed fecal bacterial composition using Histological staining and 16S rRNA sequence. DSS administration destroyed intestinal mucosal structure and changed the diversity of intestinal flora relative to control. RT-PCR and western blot confirmed specific molecular mechanisms that trigger acute inflammation and intestinal mucosal barrier function disruption after DSS treatment. And autophagy inhibition is typical pathogenesis of IBD. Interestingly, berberine ameliorates inflammation during the development of the intestinal by modulating the TLR4(Toll-like receptors 4)/NF-κB signaling pathway and activating autophagy. Berberine significantly reduces tumor necrosis factor α(TNF-α), interleukin (IL)-6, and IL-1β expression in cats' serum. Enhancing the antioxidant effect of IBD cats is one of the protective mechanisms of berberine. We demonstrated that berberine repairs intestinal barrier function by activating the mTOR(mammalian target of rapamycin) complex, which inhibits autophagy. Conclusions Berberine can restore intestinal microbiota homeostasis and regulate the TLR4/ NF-Κb pathway, thereby controlling inflammatory responses. We propose a novel mechanism of berberine therapy for IBD, namely, berberine therapy can simultaneously activate MTORC and autophagy to restore intestinal mucosal barrier function in cats, which should be further studied to shed light on berberine to IBD.